Beauty and The Best: Pembekalan bagi Victorious Women di Rock Sydney Church Australia - Claudia Angelina (Journal Of Social Empowerment Publications, 2025)
This study presents a community service activity structured as a seminar entitled Beauty and The Best: Victorious Women, held at Rock Sydney Church, Australia. The main objective of the seminar was to educate and restore the Christian understanding of true womanly beauty—not based on physical appearance or societal expectations, but grounded in spiritual identity in Christ. The method employed was an interactive lecture consisting of four key stages: biblical material preparation, seminar delivery, open discussion and Q&A, and a follow-up phase including devotional materials and the formation of a spiritual support community. The outcomes revealed a significant transformation in participants’ perception of their identity as women in Christ, along with an increased awareness of their spiritual calling within the church, family, and society. The seminar successfully fostered a reflective and encouraging environment for continuous spiritual growth among participants.